PENGARUH METODE BERMAIN TERHADAP HASIL BELAJAR MATEMATIKA KELAS III SD NEGERI 10 SIGAOL SIMBOLON - Ester Ester (JURNAL TEMATIK, 2022)
This study aims to determine whether there is an effect of the use of the play learning method on the Mathematics Learning Outcomes of Students in grade III SD Negeri 10 Sigaol Simbolon. The population is 20 people, while the data collection technique determined by the author is to use total sampling. This study uses a descriptive method. The data collected was analyzed in two ways, first descriptive analysis, which is to provide an overview/general influence of the two variables. The second stage is with inferential analysis to test the hypothesis proposed by using the Product Moment formula by Pearson, namely: Thus, the results of data analysis obtained tcount = 2.33 while ttable = 1.68 with a significance level of 5%. It turns out that tcount is greater than ttable, namely (3.33 1.68). This means that the alternative hypothesis is accepted as true. This means that there is a significant influence between the use of the play learning method on student learning outcomes in the subject matter of fractions in class III SD Negeri 10 Sigaol Simbolon